Antibiotics Associated Disorders and Post-biotics Induced Rescue in Gut Health - Paul, Debarati; Manna, Sounik; Mandal, Santi M. (Current Pharmaceutical Design, 2018)
The gut microbiota plays significant roles in the human body during all spheres' of life and influences innate immunity, promotes granulocyte signaling and provides resistance during pathogenic colonization of the gut; crucial for a healthy life. Antibiotics directly affect the gut microbiota that consequently alters the basic biological processes and imposes severe consequences in population falling under different age groups. In this article, we assessed the differences in microbial colonization and immune function of the intestinal tract in infants, adults, and the aged people and also examined the recent reports describing the impacts of antibiotics on infant microbiome assembly and functioning. The age old techniques have been compared to modern ones in relation to the functioning of the gut microbiome to draw inferences on significant impacts of various microbiota on human life starting from the womb, through infancy, adulthood and old age. It was observed that data is limited to different classes or origin of populace depicting variations in food habits and/or suffering from heavy metal associated diseases after continuous exposure to heavy metals/ metalloids/ biocides. Such extreme environmental factors significantly modulate the microbiota and assist in creating a 'co-resistant' gene pool that influences gut health. In the light of this finding, it is important to analyze the ‘co-resistant’ gene pool existing in gut-microbiome which supports to recoup and establish a healthy life. The hypothesis of ‘postbiotics’ is under process and their associations with antibiotic turn to be new-insight in antibiotic therapy. On one hand, postbiotics provide a great opportunity to understand the mechanism of action against pathobionts; on the other; they lead to postulation of newer pharmabiotic products and pharmacological strategies for better gut health.
Keywords: co-resistant